Pengaruh Sruktur Aktiva, Profitabilitas, Dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Sub Sektor Perdagangan Besar (Barang Produksi Dan Barang Konsumsi) Yang Terdaftar Di BEI - Ryko Syahputra; Intan Angelia; Lindawati Lindawati; Caroline Caroline; Noviana Noviana; Mohd. Nawi Purba (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
This study intends to examine and analyze the effect of asset structure, profitability, and firm size on the capital structure of large trading companies (production goods and consumer goods) listed on the Indonesia Stock Exchange in 2014 - 2017. The research approach used is a quantitative research and the research’s type used is descriptive research. The population used in this study is the large trading companies (manufactured goods and consumer goods) listed on the Indonesia Stock Exchange in 2014 - 2017 as many as 37 companies and obtained a sample of 15 companies multiplied by 4 years of the research period using the purposive sampling method. The coefficient of determination in this study was 32.4%, the remaining 67.6% was explained by other variables outside the study. The results of the study are based on multiple linear regression models and hypothesis testing using the f test and t-test. Asset structure and company size have a positive and significant effect on the capital structure while profitability has a negative and significant effect on the capital structure on large trading companies (manufactured goods and consumer goods) listed on the Indonesia Stock Exchange in 2014 - 2017.